2001
DOI: 10.1007/s11664-001-0154-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cu, Ag and Sb on the creep-rupture strength of lead-free solder alloys

Abstract: The materials used in the present research are pure Sn metal and Sn-0.5% Cu, Sn-3.5%Ag, Sn-0.3%Sb, and Sn-3.5%Ag-0.5%Cu alloys. Effects of Cu, Ag and Sb on the creep-rupture strength of lead-free solder alloys have been investigated. Creep tests are performed at the stress and temperature range of 3 to 12 MPa and 378 to 403 K, respectively. A 3.5% addition of Ag had the largest contribution to the creep-rupture strength of Sn metal among the single addition of 0.5%Cu, 3.5%Ag, and 0.3%Sb. The combined addition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 3 publications
1
38
0
Order By: Relevance
“…[7][8][9][10][11][12][13][14] Bismuth was a potential candidate, which can be used to form the composite lead-free solder with high reliability and low melting temperature. The reducing of melting temperature for solder alloys was reported by adding different amounts of Bi to the solder alloy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9][10][11][12][13][14] Bismuth was a potential candidate, which can be used to form the composite lead-free solder with high reliability and low melting temperature. The reducing of melting temperature for solder alloys was reported by adding different amounts of Bi to the solder alloy.…”
Section: Introductionmentioning
confidence: 99%
“…15 Microstructural evolution of solder alloys was proven to be the primary factor to influence the reliability of solder alloys. 1,[10][11][12][13][14]16 However, there is still a lack of knowledge about lead-free solders with Bi addition, especially the relationship between the microstructure of the solder alloys as a function of processing parameters and mechanical properties of the solders. Microhardness testing is considered the easiest way to determine the mechanical properties of materials, especially for solder alloys, which are composed of both soft and hard phases.…”
Section: Introductionmentioning
confidence: 99%
“…8 reveal that Cu 6 Sn 5 IMCs formed in the interfacial regions of the SAS and SAS-1In/Cu samples, but were replaced by Cu 6 (Sn,In) 5 IMCs in the SAS-5In and SAS-10In/Cu samples. EDS analysis of the Cu 6 (Sn,In) 5 IMCs in the SAS-1In, SAS-5In, and SAS-10In samples revealed the three major compositional elements of Cu/Sn/In in atomic percentages to be 51.7/46.0/0.9, 50.7/42.8/5.1, and 54.7/37.4/5.9, respectively, corresponding to IMCs of about Cu 6 Sn 5 , Cu 6 (Sn 0.9 ,In 0.1 ) 5 , and Cu 6 (Sn 0.8 ,In 0.2 ) 5 . These results indicate that the increased In content in the Cu 6 (Sn,In) 5 IMC in the SAS-10In sample is obtained at the expense of Sn content.…”
Section: Microstructure and Morphology Of Imcs At Solder/cu Interfacementioning
confidence: 98%
“…Accordingly, some researchers have investigated the feasibility of creating ternary or even quaternary Sn-based solder systems by adding alloying elements such as Cu, Ni, In, Sb, and TiO 2 to the Sn-Ag system in order to reduce the melting point and obtain a corresponding improvement in its mechanical properties. [5][6][7][8][9] Sb addition is reported to be capable of improving the mechanical properties and thermal resistance under aging. 10 In previous studies by our group, it was shown that the addition of small amounts of Sb to eutectic Sn-3Ag solder suppresses the growth of intermetallic compounds (IMCs) within the solder matrix as a result of a pinning effect at the grain boundary.…”
Section: Introductionmentioning
confidence: 99%
“…4 Therefore, the creep study of tin-antimony alloys has received a great deal of attention. 1,2,[5][6][7] The general conclusion is that while antimony atoms in solution have only a minor effect on the creep resistance, alloys with higher concentrations of antimony contain cuboid and whisker-type SnSb precipitates, which provide a significant composite strengthening effect that reduces the creep rate of the material especially at temperatures below 100°C.…”
Section: Introductionmentioning
confidence: 99%